Penetapan Kebutuhan Harian Pakan Ikan Rucah untuk Penggemukan Kepiting Bakau Scylla paramamosain di Keramba Jaring Dasar - Sandi Permadi; Sri Juwana, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Determination of Daily Requirement of Trash Fish Feed to Fatten The Mangrove Crab Scylla paramamosain in Bottom Net Cages. Mangrove crab fattening is part of the crab farming activities that attracts the interests of the farmers due to its relatively short period, i.e. 14–21 days per cycle. Trash fish is a natural feed for Mangrove crabs that is easily available at an affordable price. Scientific information on the daily requirement of trash fish feed to fatten the Mangrove crabs is still scarce. The accessable scientific information on the amount of daily feeding is still limited to the rearing of the crabs. Hence, the scientific study on the daily requirement of trash fish feed for crab fattening needs to be done. Probolinggo is one of the producing districts for Mangrove crabs and is a potential area for development of crab aquaculture. Therefore, Probolinggo was chosen as the site of this research. Crab samples utilized had a carapace width of 8–13 cm and a weight of 115–500 g. Crabs were reared in bottom net cages measuring 5 x 5 m2 with a density of 16 crabs/cage and the sex ratio of 1: 1. The study consisted of 4 treatments with 3 repetitions. The daily feeding percentages given were 10, 15, 20, and 25% of the body weight of the crabs. The parameters observed during the 13 days of experiment were growth, survival rate, and the percentage of already fatter crabs. The results showed that the daily feed ration of trash fish, as much as 10% dan 15% of the body weight of the crab, gave the best yield for crab fattening. The survival rate obtained was 70% of the initial density of 0.64 crabs/m2, with a total weight gain of 14% during the study.